Efficacy of native phosphate-solubilizing rhizobia on symbiotic parameters and grain yield in fieldpea (Pisum sativum) - Khanna, Veena; Simmi, Simmi; Sharma, Poonam; Jindal, Chintu; Saxena, A K (The Indian Journal of Agricultural Sciences, 2012)
The native P-solubilizing rhizobial isolates R1 and R2 enhanced nodule number and dry weight, root and shoot dry weight, chlorophyll, N and P content and grain yield as compared to non P- solubilizing rhizobia. Native rhizobia R1 and R2 along with P @ 40 kg P2O5/ha were found to augment the efficiency of applied P which enhanced symbiotic parameters and significantly improved yields of fieldpea.